Mental health and work: Switzerland (Paris, 2013)
"Tackling mental ill-health of the working-age population is becoming a key issue for labour market and social policies in OECD countries. OECD governments increasingly recognise that policy has a major role to play in keeping people with mental ill-health in employment or bringing those outside of the labour market back to it, and in preventing mental illness. This report on Switzerland is the fifth in a series of reports looking at how the broader education, health, social and labour market policy challenges identified in Sick on the Job? Myths and Realities about Mental Health and Work (OECD, 2012) are being tackled in a number of OECD countries. It concludes that the Swiss system is well resourced to address the challenges in various policy fields; that due the involvemnet of a large number of stakeholders much needed policy coordination across different sectors is a difficult task; and that a stronger mental health focus is required in Switzerland's health, social and labour market policies."